Screening for Sarawak Paddy Landraces with Resistance to Yellow Rice Stem Borer, Scirpophaga incertulas (Walker) (Lepidoptera: Crambidae) - Ling, Alvin Xian Rong; Yeo, Freddy Kuok San; Nur Najwa, Hamsein; Ting, Hieng Ming; Mogeret, Sidi; Wan Nurainie, Wan Ismail; Annebell Stphanie, Taji; Cheok, Yin Hui (Universiti Putra Malaysia Press, 2020)
The yellow rice stem borer, Scirpophaga incertulas (Walker) is a prevalent pest in paddy fields worldwide. In Sarawak, a survey on pest of paddy carried out from 2009 to 2011 covering 166 paddy fields revealed that rice stem borers caused 11.4% of total paddy damage. In order to reduce the damage, identifying resistance paddy variety is crucial. The objective of this study was to screen Sarawak paddy landraces with resistance to S. incertulas.Twelve Sarawak paddy landraces were selected randomly for this study. Antixenosis resistance screening was performed in aquariums (60 x 28 x 33 cm). Three replications of one-monthold seedlings were randomly arranged in aquarium and exposed to adult S. incertulas. The number and position of egg mass on each plant were recorded. Egg mass abnormalities were also observed. For antibiosis, rice culms of two-month old seedlings from each landrace were infestedwith larvae. The length of surviving larvae from five rice culms was measured. The experiment revealed variations in landraceof preference for ovipositing. Among the twelve Sarawak paddy landraces, Kanowit was more preferred by S. incertulas for ovipositing in comparison to other paddy landraces suggesting susceptibility towards the pest. Abaxial leaf surface was the preferred oviposition site. There was no clear antibiosis response of the paddy landraces towards S. incertulas larvae in this study.